Edukasi Fisioterapi Untuk Meningkatkan Pemahaman Masyarakat Tentang OA Knee dan Penatalaksanaannya di Puskesmas Kendalsari Kota Malang - Rahmawati, Angelia Pramita; Rahmanto, Safun; Suharto, Bonita (Rena Cipta Mandiri, 2025)
Osteoarthritis of the knee (OA Knee) is a degenerative disorder of the joints that is commonly experienced by adults to the elderly, which causes pain, stiffness, and limited movement that hinders daily activities. Public understanding of proper physical exercise is needed to slow the development of OA Knee and maintain knee joint function. This counseling activity aims to provide education about OA Knee, including the introduction of risk factors, clinical symptoms, prevention efforts, and examples of exercises that are easy to do at home. Counseling is carried out through education using leaflet media, interactive discussions such as questions and answers to explore problems faced by participants, and direct practice of exercises that can be done at home independently such as active passive knee flexion, seated knee extension, SLR, Retrowalking. During the activity, the community showed a significant increase in knowledge, from previously not understanding to increasing their understanding, so it is hoped that the application of the exercises provided can help reduce the incidence and severity of OA Knee in the community around the Kendalsari Health Center, Malang City.